The Role of Choline (B4) in Muscle and Heart Health and Its Function - A Narrative Review - Korohod, Tamara; Pietrzak-Chmiel , Martyna; Ramaneckaite, Paulina; Binkiewicz, Agnieszka; Ślesik, Maciej (Journal of Education, Health and Sport, 2026)
Background: Choline is an essential micronutrient critical for neurotransmitter synthesis, lipid metabolism, and cellular function. Evidence demonstrates its vital importance for skeletal muscle and cardiac function. Objective: This narrative review analyzes choline's role in muscle and cardiac health, the biochemical mechanisms supporting muscle contraction and cardiac function, and practical implications for athletes and cardiovascular patients. Methods: Systematic search of PubMed, Scopus, and Web of Science (2026) using keywords: choline, muscle health, acetylcholine, cardiac function, muscle contraction, cardiomyopathy and supplementation. Priority given to randomized controlled trials, mechanistic studies, and systematic reviews. Results: Choline serves as a precursor to acetylcholine (ACh), the primary neurotransmitter for neuromuscular transmission and muscle contraction initiation [1–4]. Deficiency is associated with reduced strength and impaired nerve-muscle signaling [1,2,5–8]. Chronic deficiency decreases phosphatidylcholine synthesis, impairing muscle membrane integrity [9–11]. In cardiac health, choline and betaine lower homocysteine levels, a cardiovascular risk factor [12–14], and demonstrate cardioprotective effects through oxidative stress reduction and enhanced parasympathetic function [15–17]. Adequate intake (550 mg/day men; 425 mg/day women) is obtained through meat, seafood, eggs, legumes, and cruciferous vegetables [18–20]. Choline supplementation may improve endurance performance during intense exercise exceeding 2 hours [21,22]. Conclusions: Choline is essential for muscle health as an acetylcholine precursor and membrane lipid component, supporting contraction and protein synthesis. For cardiac health, choline reduces disease risk by lowering homocysteine and reducing oxidative stress. Adequate choline is vital for athletic performance and may support cardiac function in cardiovascular disease patients.